Mean Streak - Brown, Sandra 1948- (New York : Grand Central Publishing, 2014)
"Dr. Emory Charbonneau, a pediatrician and marathon runner, disappears on a mountain road in North Carolina. By the time her husband Jeff, miffed over a recent argument, reports her missing, the trail has grown cold. Literally. Fog and ice encapsulate the mountainous wilderness and paralyze the search for her. While police suspect Jeff of "instant divorce," Emory, suffering from an unexplained head injury, regains consciousness and finds herself the captive of a man whose violent past is so dark that he won't even tell her his name. She's determined to escape him, and willing to take any risks necessary to survive. Unexpectedly, however, the two have a dangerous encounter with people who adhere to a code of justice all their own. At the center of the dispute is a desperate young woman whom Emory can't turn her back on, even if it means breaking the law. As her husband's deception is revealed, and the FBI closes in on her captor, Emory begins to wonder if the man with no name is, in fact, her rescuer"--
Library Journal
Kirkus Reviews
Publishers Weekly
Library Journal Prepub Alert
Adult.
Adult.
Keywords: Man-woman relationship -- Fiction; Missing persons -- Fiction; Kidnapping -- Fiction; Adventure fiction; North Carolina -- Fiction